The Islamic University - Fadlullah Wilmot (International Institute of Islamic Thought, 1990)
In order to promote a better and more comprehensive understanding of an International Islamic University within the dynamic socio-cultural setting of the contemporary world, the International Islamic University held a fourday seminar during Muharram 8-10, 1410/August 10-14, 1989. The seminar was also designed to look at the inunediate and long-term development plans and strategies of the University to ensure that high international standards are maintained as well as practical relevance to the local socio-politicoeconomic environment. The Islamization of knowledge has multifaceted dimensions and implications for scholars in developing the integrated university curriculum with the appropriate teaching materials and the achievement of moral-intellectual excellence. Originally planned as an internal affair, the seminar generated interest among the academic community in Malaysia and neighboring countries so that it finally involved over 600 participants, including the academic staff of the University. There were 26 speakers from various countries and disciplines. Professor Abdul Hamid AbuSulayman in his introduction mentioned the need for Muslims to regain the intellectual dimension. He emphasized that Islamization of knowledge is not confined to the Shari'ah disciplines Islamic thought integrates two sources of knowledge-revealed knowledge and human knowledge. He mentioned the plan of the University to introduce a system whereby graduates could, in five years, obtain two degrees-one in revealed and one in worldly knowledge. In his usual erudite and scholarly manner Professor al-Attas discussed the purpose of the university and the Islamic concept of knowledge. He emphasized that the division into fardhu 'ain and fardhu kifayyah did not imply that there was no connection between the two but the division was a moral one in order to prevent compulsory knowledge being absorbed into worldly knowledge. Professor al-Attas clarified that in order to understand what we want from a university we must first understand the nature of mankind and in order for us to understand the nature of mankind we must understand the Qur'anic teaching regarding human beings, which deals not only with the body but also with the soul ...